2018
DOI: 10.15171/jpid.2017.003
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitude of Iranian Dentists towards Peri-implant Diseases

Abstract: Background. Despite successful results of implant therapy, complications occasionally occur in challenging situations.Apart from academic courses for implantology, dental associations also offer training courses for general practitioners.We sought to assess dentists' attitude towards peri-implant diseases. Methods. The subjects in thisquestionnaire-based cross-sectional study consisted of dentists participating in the annual congress of the Iranian Dental Association in 2013, whose knowledge and attitudes towa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Four of the included studies were papers from consensus conferences [18-20,23]; two of them suggested diagnostic guidelines [24,25], three authors suggested the classification of peri-implantitis [3,21,26], and another suggested the index of implant success (Table 1) [22]. …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Four of the included studies were papers from consensus conferences [18-20,23]; two of them suggested diagnostic guidelines [24,25], three authors suggested the classification of peri-implantitis [3,21,26], and another suggested the index of implant success (Table 1) [22]. …”
Section: Resultsmentioning
confidence: 99%
“…In cases of failure the implant presents pain, exudate, mobility, and bone loss > 1/2 the length of the implant. Kadkhodazadeh et al [22] presented the implant success index, a scoring system to evaluate the clinical outcomes of dental implants that includes the evaluation of soft-tissue level, PD, BOP, hard-tissue level, and radiographic bone loss detected via a long-cone parallel periapical technique. According to these evaluations, implants may be classified into eight groups: clinically healthy, soft-tissue inflammation, deep soft-tissue pockets (PD > 4 mm), initiation of hard-tissue breakdown, hard-tissue breakdown plus soft-tissue recession, notable hard-tissue breakdown, notable hard-tissue breakdown plus soft-tissue recession, severe bone loss, and clinical failure implants presenting with mobility (Table 1) [22].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations